2016
DOI: 10.1016/j.acap.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Admission to Hospital: A Mixed Methods Survey of Pediatric Practices, Benefits, and Challenges

Abstract: Background Direct admissions account for 25% of pediatric unscheduled hospitalizations. Despite this, our knowledge of direct admission practices and safety is limited. This study aimed to characterize direct admission practices, benefits and challenges at a diverse sample of hospitals, and to identify diagnoses most appropriate for this admission approach. Methods We conducted a national survey at a stratified random sample of 177 US hospitals, employing both closed- and open-ended questions. Descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…13 These quantitative data are mirrored in a national survey of pediatric medical directors reporting direct admission rates at their hospitals that range from less than 10% to greater than 50%. 16 Despite this, only one-third report having formal direct admission policies in place, while 50% report a belief that more children should be admitted directly. This significant variation across hospitals and conditions indicates clinical uncertainty regarding hospital admission best practices.…”
Section: Introductionmentioning
confidence: 99%
“…13 These quantitative data are mirrored in a national survey of pediatric medical directors reporting direct admission rates at their hospitals that range from less than 10% to greater than 50%. 16 Despite this, only one-third report having formal direct admission policies in place, while 50% report a belief that more children should be admitted directly. This significant variation across hospitals and conditions indicates clinical uncertainty regarding hospital admission best practices.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, there are also risks and potential harms associated with direct admission, including potential delays in initial evaluation and management, inconsistent admission processes, and difficulties determining direct admission appropriateness, all of which could adversely impact patient safety and quality of care. 7-9 One study of adults with sepsis found that direct admission was associated with increased mortality compared to ED admission, which the authors speculated to be related to less timely care.…”
mentioning
confidence: 99%
“…In our national survey of pediatric direct admission guidelines, less than one-third of hospitals reported having formal criteria to assess the appropriateness of direct admissions, and respondents’ perspectives regarding populations and diagnoses appropriate for this admission approach varied considerably. 7 These results point to the need for further research and quality improvement initiatives to inform the development of direct admission guidelines and protocols.…”
mentioning
confidence: 99%
See 2 more Smart Citations